The Role of Short TAU Iversion Recovery (STIR) Sequence in Lumbar MRI Examinations at Andalas University Hospital - Hanifah, Wahdini; Dewilza, Nerifa; Yudha, Sagita; Nisa, Chairun; Arkananta, Faiz (Oshada, 2026)
Magnetic Resonance Imaging (MRI) is a non-invasive diagnostic imaging modality that excels in displaying details of the body's soft tissues, including the lumbar spine area. One important sequence in a lumbar MRI examination is the Short Tau Inversion Recovery (STIR) which functions to suppress fat signals to increase the contrast between normal and pathological tissue. This study aims to determine the management of lumbar MRI examinations and analyze the role of the STIR sequence in detecting abnormalities in patients with clinical Low Back Pain (LBP) and Herniated Nucleus Pulposus (HNP). This study used a descriptive method with a qualitative approach at Andalas University Hospital in August 2025, Research Informants numbered 4 people, consisting of 2 radiographers, 1 Radiology doctor, and 1 head of the room. Data collection was carried out through in-depth interviews, observation, and documentation, then analyzed using source triangulation techniques and presented in tabular form. The results show that the STIR sequence is routinely used in sagittal and coronal sections. STIR plays a crucial role in homogenously suppressing fat signals, enhancing tissue contrast, and detecting edema, inflammation, and abnormalities in the spinal cord more clearly than other sequences such as T1, T2, and Fatsat. Although STIR has the drawback of a low Signal-to-Noise Ratio (SNR) and longer scan times, the overall image quality is considered optimal and very helpful in establishing radiological diagnoses. Therefore, the STIR sequence plays a crucial role in lumbar MRI examinations, especially in cases involving bone marrow and soft spinal tissue.